Relationship between the brand identity with brand loyalty due to the mediating role of perceived value - Reza Abedi; Fereydoon Azma (Dutch Journal of Finance and Management, 2019)
The aim of present study was to investigate the relationship between brand identity with brand loyalty regard to the mediating role of perceived value of the brand, brand trust, and customer satisfaction of brand. The research method was descriptive/monitoring -correlation type. The population was all customers of Sabah Dairy Company in Golestan province, Iran that 384 individuals were determined as the sample size and sampling was clustering method. The research tools were following questionnaires standard brand identity by "Bhattacharya and Sen", brand loyalty, brand trust and brand customer satisfaction by He et al., brand equity by Nam et al., standardized questionnaire of brand perceived value by Lasar et al. The reliability of the questionnaire using Cronbach's alpha coefficient were calculated 0.844, 0.815, 0.661, 0.859, 0.724 and 0.885 for brand identity, perceived value of the brand, brand customer satisfaction, brand trust, brand loyalty and brand equity, respectively and the validity of questionnaires was approved with convergent validity method. The results showed that there was significant relationship between the brand identity with brand loyalty due to the mediating role of perceived value, trust and satisfaction.
Keywords: 650; brand identity; brand loyalty; brand equity; perceived value of the brand; brand trust; brand customer satisfaction